Evaluating NfL and NTproBNP as predictive biomarkers of intracranial injuries after mild traumatic brain injury in children presenting to emergency departments - Chiollaz, Anne-Cécile; Pouillard, Virginie; Seiler, Michelle; Habre, Céline; Romano, Fabrizio; Ritter Schenck, Céline; Spigariol, Fabian; Korff, Christian; Maréchal, Fabienne; Wyss, Verena; Gruaz, Lyssia; Montaner, Joan; et al. (Frontiers in Neurology, 2025)
ObjectiveBlood-biomarkers have the potential to aid clinicians in pediatric emergency departments (PED) in managing children with mild traumatic brain injury (mTBI) acutely. However, studies focusing on pediatric populations remain limited. We aim to assess the performances of two routinely used biomarkers in other fields: the neurofilament light chain protein (NfL), and the N-terminal prohormone of brain natriuretic peptide (NTproBNP), to safely discharge children without intracranial injuries (ICIs).MethodsA prospective multicenter cohort study was conducted, enrolling children suffering from mTBI, both with and without imaging during their acute management in the PED. A blood sample was collected within 24 h post-trauma for biomarker analysis. Inclusion criteria followed the PECARN (Pediatric Emergency Care Applied Research Network) guidelines for the diagnosis of mTBI and for ICI on CT as the primary outcome (CT+).ResultsA total of 302 mTBI patients were analyzed comparing children with ICI (18 CT+) versus all the other children without ICI (54 CT− and 230 in-hospital-observation patients without CT). NfL and NTproBNP were increased in the CT+ group and their performances to safely rule-out patient without ICI reached up to 30% specificity with 100% sensitivity. Equivalent performances were observed whether selecting patients with blood collection within 6 h or 24 h post-trauma.ConclusionNfL and NTproBNP were described for the first time in children suffering mTBI. Their performances were comparable to well-known biomarkers, such as S100b, GFAP, or HFABP, with the benefit of already being used in routine tests for other diseases. Further large-scale studies are necessary to verify and validate these results.